Description of new species of Pseudamaurops Jeannel, 1948 (Coleoptera: Staphylinidae: Pselaphinae) from Greece and North Macedonia - Bekchiev, Rostislav; Hlaváč, Peter (Zootaxa, 2019)
Two new species of Pseudamaurops Jeannel, 1948 are described, P. hristovskii sp. n. from North Macedonia and P. tymficus sp. n. from Greece. Redescriptions of P. albanicus (Apfelbeck, 1907) and P. muellerianus (Ravasini, 1923) are provided, and an identification key for the genus is provided.